PENGARUH SUPERVISI AKADEMIK TERHADAP KINERJA GURU DI SDN 5 GUNUNG PERENG CILEMBANG KOTA TASIKMALAYA - Mukaromah, Laili Lailatul; Wartim; Putri, Agi Mahesa (Institut Nahdlatul Ulama Tasikmalaya, 2024)
Supervision is the process by which principals oversee, guide and direct the performance of teachers, staff and other employees in the school environment. A good and effective educational institution requires qualified and competent teachers in their fields, as well as professional principals. The implementation of an academic supervision program that is carried out consistently and seriously by the principal will result in a continuous evaluation process that can encourage improved teacher performance. This study aims to determine academic supervision, teacher performance, and how much influence academic supervision has on teacher performance. The method used is a survey method with a quantitative approach with a sample of 15 teachers including the principal of SDN 5 Gunungpereng Cilembang Tasikmalaya City through a questionnaire. The results of the analysis show that academic supervision at SDN 5 Gunungpereng Cilembang Tasikmalaya City is in the good category with an average value of 0.804. Teacher performance is in the good category with an average value of 0.786. There is a positive and significant influence between academic supervision on teacher performance at SDN 5 Gunungpereng Cilembang, Tasikmalaya City with a regression value of 0.877 and a significant level of 0.000. Academic supervision contributes 76.9% to teacher performance, the remaining 23% is influenced by other variables. This finding has implications for educational institutions in prioritizing the quality of academic supervision as a teacher performance measure.